Evolutionary History of DNA Methylation Related Genes in Bivalvia: New Insights From Mytilus galloprovincialis - Gerdol, Marco; La Vecchia, Claudia; Strazzullo, Maria; De Luca, Pasquale; Gorbi, Stefania; Regoli, Francesco; Pallavicini, Alberto; D’Aniello, Enrico (Frontiers in Ecology and Evolution, 2021)
DNA methylation is an essential epigenetic mechanism influencing gene expression in all organisms. In metazoans, the pattern of DNA methylation changes during embryogenesis and adult life. Consequently, differentiated cells develop a stable and unique DNA methylation pattern that finely regulates mRNA transcription during development and determines tissue-specific gene expression. Currently, DNA methylation remains poorly investigated in mollusks and completely unexplored in Mytilus galloprovincialis. To shed light on this process in this ecologically and economically important bivalve, we screened its genome, detecting sequences homologous to DNA methyltransferases (DNMTs), methyl-CpG-binding domain (MDBs) proteins and Ten-eleven translocation methylcytosine dioxygenase (TET) previously described in other organisms. We characterized the gene architecture and protein domains of the mussel sequences and studied their phylogenetic relationships with the orthologous sequences from other bivalve species. We then comparatively investigated their expression levels across different adult tissues in mussel and other bivalves, using previously published transcriptome datasets. This study provides the first insights on DNA methylation regulators in M. galloprovincialis, which may provide fundamental information to better understand the complex role played by this mechanism in regulating genome activity in bivalves.